Lipid‐Bilayer‐Supported 3D Printing of Human Cerebral Cortex Cells Reveals Developmental Interactions. Issue 31 (14th June 2020) - Zhou, Linna; Wolfes, Anne C.; Li, Yichen; Chan, Danny C. W.; Ko, Ho; Szele, Francis G.; Bayley, Hagan
Abstract: Current understanding of human brain development is rudimentary due to suboptimal in vitro and animal models. In particular, how initial cell positions impact subsequent human cortical development is unclear because experimental spatial control of cortical cell arrangement is technically challenging. 3D cell printing provides a rapid customized approach for patterning. However, it has relied on materials that do not represent the extracellular matrix (ECM) of brain tissue. Therefore, in the present work, a lipid‐bilayer‐supported printing technique is developed to 3D print human cortical cells in the soft, biocompatible ECM, Matrigel. Printed human neural stem cells (hNSCs) show high viability, neural differentiation, and the formation of functional, stimulus‐responsive neural networks. By using prepatterned arrangements of neurons and astrocytes, it is found that hNSC process outgrowth and migration into cell‐free matrix and into astrocyte‐containing matrix are similar in extent. However, astrocytes enhance the later developmental event of axon bundling. Both young and mature neurons migrate into compartments containing astrocytes; in contrast, astrocytes do not migrate into neuronal domains signifying nonreciprocal chemorepulsion. Therefore, precise prepatterning by 3D printing allows the construction of natural and unnatural patterns that yield important insights into human cerebral cortex development. Abstract : The human cerebral cortex contains distinguishable cell arrangements that are important for brain function. The 3D droplet printing technique reported allows the assembly of human cortical neurons and glial cells into defined patterns in extracellular matrix. The engineered human cortical tissues are functional and able to recapitulate aspects of brain development.